2015
DOI: 10.3390/molecules20045965
|View full text |Cite
|
Sign up to set email alerts
|

A New 9,10-Dihydrophenanthrene and Cell Proliferative 3,4-δ-Dehydrotocopherols from Stemona tuberosa

Abstract: A new compound, 9,10-dihydro-5-methoxy-8-methyl-2,7-phenanthrenediol (1), was isolated from the roots of Stemona tuberosa Lour. (Stemonaceae) together with two new optically active compounds, (2S,4'R,8'R)-3,4-δ-dehydrotocopherol (2) and (2R,4'R,8'R)-3,4-δ-dehydrotocopherol (3). The structures of compounds 1–3 were determined on the basis of spectroscopic data analysis. Compounds 2 and 3 were each purified from a stereoisomeric mixture of 2 and 3 by preparative HPLC using a chiral column for the first time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…These results match those previously reported by other researchers, which highlighted an anti-proliferative activity of phenanthrenes and 9,10-dihydrophenanthrenes on several cancer cell lines derived from different tumor types, such as leukemia, breast, colon, prostate, and lung cancer [10,55]. Notably, several papers reported that similar molecules, at comparable doses, are effective on cancer cells and well tolerated by normal cells, suggesting a possible selective toxicity [56][57][58][59].…”
Section: Anti-proliferative Effects On Gastric Cancer Cell Linessupporting
confidence: 91%
“…These results match those previously reported by other researchers, which highlighted an anti-proliferative activity of phenanthrenes and 9,10-dihydrophenanthrenes on several cancer cell lines derived from different tumor types, such as leukemia, breast, colon, prostate, and lung cancer [10,55]. Notably, several papers reported that similar molecules, at comparable doses, are effective on cancer cells and well tolerated by normal cells, suggesting a possible selective toxicity [56][57][58][59].…”
Section: Anti-proliferative Effects On Gastric Cancer Cell Linessupporting
confidence: 91%
“…Alkaloid and stilbenoid isolated from the root of Stemona tuberosa are reported to have anti-inflammatory [306] and antibacterial [307] effects, while the dehydrotocopherol derivatives have been found to scavenge oxygen and free radicals [308]. Tocopherols isolated from the root of Stemona tuberosa increase cell proliferation in the mouse fibroblast NIH3T3 cells, suggesting the potential use of these compounds as wound healing agents [309].…”
Section: Traditional Use Of Medical Plants In Wound Healingmentioning
confidence: 99%
“…20,21 g-Dehydrotocopherol shows proliferative effects on mouse NIH 3T3 broblasts and a potential use as wound healing agent has been suggested. 21 As mentioned above, a-, b-, gand d-tocotrienols (14, 15, 16, 17) usually occur as trace vitamers, however, several plant tissues and oils accumulate higher amounts of tocotrienols. For example, a-tocotrienol was found in barley (76 mg/100 g), gand d-tocotrienol in palm oil (36 mg and 8 mg/100 g, respectively).…”
Section: Plantsmentioning
confidence: 99%
“… 20,21 γ-Dehydrotocopherol shows proliferative effects on mouse NIH 3T3 fibroblasts and a potential use as wound healing agent has been suggested. 21 …”
Section: Meroditerpenesmentioning
confidence: 99%